Zinc oxide/Polypyrrole particle-decorated rod structure for NO2 detection at low temperature - Thanh Dong, Vu; Tien Hung, Pham; Duc Anh, Le; Quoc Vuong, Ly; Duy Khanh, Dang; Thi Huong, Nguyen (Vietnam Journal of Science and Technology, 2024)
In this study, Zinc oxide (ZnO) nanoparticles with a size of about 50 - 70 nm were green-synthesized using tea leaves and ZnO/Polypyrrole (ZnO/Ppy) nanocomposites were obtained by ultrasonic-assisted chemical polymerization method using pyrrole monomer and the nanoparticles. The characterization of the materials is conducted using several analytical techniques, including Field Emission Scanning Electron Microscopy (FESEM) and X-Ray Diffraction (XRD) and Ultraviolet visible spectrum (UV-Vis). The synthesized PPy material exhibits have a rod-shaped structure, diameter ranging from 100 to 200 nm. The ZnO/PPy nanocomposite system, consisting of PPy rods surrounded by ZnO particles. The gas sensing characteristics of the materials have also been investigated by measuring their sensitivity, response time, and stability to NO2 at low temperature and different humidity. Notably, the material exhibits considerable sensitivity to NO2 gas at low temperatures and the parameters related to response and recovery times are relatively rapid. Furthermore, a potential gas-sensing mechanism based on changes in the width of the depletion region is proposed.